2021
DOI: 10.23960/jipt.v9i1.p62-71
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Value of Fermented Banana Peels using Different Levels of Palm Sap

Abstract: Banana peels are banana processing wastes that can be used as poultry feedstuff, but bacause of its high crude fiber content, so to reduce the high crude fiber content it need processing such as fermentation. Fermentation process requires soluble carbohydrates such as palm sap. This research aimed to evaluate the effect of different levels of palm sap as an additive on the nutrient composition of banana peels. An experimental method was used in this research with a completely randomized design consisted of fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 2 publications
1
7
1
1
Order By: Relevance
“…The increase in PSL, caused reducing in ash content. This is different from the results of research by Koni et al [8] on fermentation of kepok banana peels with different levels of palmyra sap, increasing of addition of palm sap, could increase ash content in the banana peel silage.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The increase in PSL, caused reducing in ash content. This is different from the results of research by Koni et al [8] on fermentation of kepok banana peels with different levels of palmyra sap, increasing of addition of palm sap, could increase ash content in the banana peel silage.…”
Section: Resultscontrasting
confidence: 99%
“…Reddy and Pierson [7] states that the fermented enhances or creates a unique taste, changes the texture properties, and improves nutritional quality and digestibility. The decrease in crude fiber can be done through the fermentation process, as reported from 18.71 to 11.55 after being fermented with palm sap [8], fermented with EM4 from 12.36 to 10.92% [9], from 18.71 to 12.02% after being fermented for 6 days with 10% goat rumen fluid [10].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing dragon fruit peel waste in the food business has gained popularity recently, notably for the creation of beneficial foods and drinks. This is consistent with the rising trend of consumers who are concerned about their health and the environment [6]. The food sector produces a lot of banana peel waste, which has the potential to be used in a variety of ways.…”
Section: Introductionsupporting
confidence: 74%
“…Helda and Sabuna (2012) found that using 15% palmyra sap in the fermentation of goat and chicken feces increased the crude protein content and reduced the crude fiber content from 13.7% to 15.8% and from 8.01% to 6.96%, respectively. Similarly, Koni et al (2021), reported that the crude fiber content of banana peels decreased from 18.7% to 11.6% after 6 days of fermentation with 20% palmyra sap. In addition to carbon sources, the fermentation process requires protein sources, such as non-protein nitrogen, which can be used by microorganisms.…”
Section: Introductionmentioning
confidence: 88%